Anal Atresia in Canines - Microsurgery for Treatment - Caye, Pâmela; da Silva Reinstein, Rainer; Nascimento Antunes, Bernardo; Basso Cartana, Camila; Carlos Gasparotto, Jean; Reginato Martins, Leticia; Pivoto Herbichi, Alana; Veloso Brun, Maurício (Acta Scientiae Veterinariae, 2024)
Background: Anal atresia is the most common anorectal malformation in dogs. The treatment of choice for this type of deformity is surgical, with the possibility of postoperative complications. Hyperbaric oxygen therapy (HBOT) consists of offering 100% oxygen in pressurized environments. HBOT causes tissue hyperoxygenation, stimulation of fibroblast angiogenesis and tissue proliferation and is recommended for tissue injuries and for cicatrisation. This work describes the surgical correction of cases of anal atresia in 2 young dogs, 1 of which is associated with a rectovaginal fistula, using microsurgical techniques. In addition, it also describes the associated complications, such as rectal stenosis and vaginal prolapse. Cases: Case 1. Describes a 21-day-old, mixed-breed male dog, with no fecal elimination since birth, caused by type III anal atresia. The patient was submitted to the procedure using a surgical microscope with 10x magnification. The skin and subcutaneous tissue were incised over the anal dimple area and the rectum was located and incised up to the lumen. The mucocutaneous suture was performed in a simple isolated pattern with 6-0 polydioxanone, circling the rectal access at 360°. Subsequently, he developed anal stenosis, treated with anal dilation procedures using balloon endotracheal tubes and enemas. The patient died at home, with no possibility of confirming the cause of death. Case 2. Reports the micro-surgical procedure performed on a 60-day-old bitch with type III anal atresia associated with a rectovaginal fistula. The procedure started with episiotomy to identify the presence of communication of the roof of the vagina and the ventral wall of the rectum. The communication was identified with approximately one centimeter of depth. Ligature was performed for occlusion of the rectovaginal communication, with 6-0 polydioxanone. Anal atresia was corrected in a manner similar to that previously described, with a cross cutaneous incision in the anal dimple area. After identification of the rectum, an incision up to the lumen was performed followed by a 360° mucocutaneous suture using 6-0 polydioxanone thread in a simple isolated pattern. The vaginal roof was reconstructed. The patient presented stitches dehiscence treated conservatively and with an association of 2 sessions of hyperbaric oxygen therapy at 2ATA. After 250 days, the patient developed vaginal prolapse type III and was subjected to clinical therapy and ovariectomy. Conservative treatment did not have the expected effect. Therefore, the patient was referred for vaginal ressection with vulvoplasty. The patient is clinically stable 900 days after the last surgical procedure. Discussion: The greatest difficulty is the presence of delicate tissues and impaired visualization due to the location of the blind end of the rectal pouch within the pelvic cavity. The surgeries were considered satisfactory and the postoperative complications were consistent with what was reported in the literature. The use of microsurgery provided excellent visualization of the structures, preservation of the anal sphincter in case 2, and precise mucocutaneous suture. HBOT helped the patient’s healing process. This is the 1 st report of vaginal prolapse in a bitch with anal atresia. It is concluded that the microsurgery is an excellent tool for the treatment of anal atresia in dogs. Keywords: anorectal malformation, surgical microscope, veterinary surgery, vaginal prolapse.